Klang River Water Quality Assessment and Its Effects on Human Health Using Chemometric Analysis - Tengku Ibrahim, Tengku Nilam Baizura; Andrison Anak Jesi; Nur Azalina Suzianti Feisal; Yuanita Windusari; Nursalfarina Abdul Samat; Noor Haziqah Kamaludin; Norfadillah Derahim; Mohd Azwan Ahmad; Tengku Norbaya Tengku Azhar (Universitas Airlangga, 2024)
Introduction: River water pollution has been a significant hazard to human health and is associated with severe health risks. This study evaluates water quality and heavy metal levels in the Klang River, analyzing their health risks through chemometric analysis. Methods: Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) was used to analyse the heavy metal contents in river water samples obtained from 9 sampling stations. Chemometric statistical techniques (principal component analysis (PCA) and hierarchical cluster analysis (HCA)) are employed to identify the sources of physicochemical properties and heavy metals. The human health risk was evaluated using statistical analysis, apart from hazard quotient (HQ), hazard index (HI), and carcinogenic risk (CR). Results and Discussion: Results showed that the physicochemical parameters were within acceptable limits. The concentration of heavy metals was found to follow a decreasing order of As > Ni below permissible levels, except at P9 and P8. PCA and HCA showed important connections among parameters, emphasizing that COD, NH3N, and TDS are key factors affecting Klang River water quality. Conclusion: The study assesses pollution risks in the Klang River, offering crucial insights for sustainable estuary management. It highlights significant changes in temperature, pH, TDS, BOD, DO, and NH3N levels, along with specific trends in heavy metal concentrations. The Health Risk Assessment indicates acceptable HQ and Target Cancer Risk values. However, the study's limited sample sites and focused timeframe might hinder understanding long-term patterns and regional differences. Extended data collection and additional information are necessary to improve water quality management and protect public health